Assessment the Social Determinants of Health in Pregnant Women Referring to Mashhad educational Hospitals in 2019 - Ghaffari Sardasht 1*, Fatemeh; Keramat 2, Afsaneh (Shahroud Journal of Medical Sciences, 2019)
Background: Being a mother is sweetest experience of women in her life. Nevertheless, it may also prove unpleasant owing to a wide range of factors that put a mother's life and health at risk during pregnancy and delivery. The aim of study was to identify the social determinants of health in pregnant women referring to Mashhad educational hospitals in 2019. Methods: The research sample in this descriptive study comprises 1020 pregnant women who were monitored and visited at Mashhad educational hospitals. Data was collected by means of personal and midwifery application forms and, subsequently, analyzed by SPSS®-v20 software. Significant level was set at 0.05. Results: According to the results, the cases studied were confronted with social factors such as spouse unemployment (4.6%), spouse illiteracy (5%), personal illiteracy (5%), bad hygiene behaviors (10.5% with smoking habit), and drug abuse (2.2%). At the same time, 19% of the cases had no insurance coverage. Conclusions: In addition to the common pregnancy and labor risks, pregnant women are challenged by issues such as poverty, unemployment, and illiteracy that significantly affect their life-quality as well as their ability to improve their health standard. Keywords: Health Social Determinants, Pregnant Women, Educational Hospitals.